Strategi Komunikasi Dinas Pariwisata Kabupaten Karangasem dalam Meningkatkan Kunjungan Wisata Pasca Erupsi Gunung Agung - Adnyaswari, Ketut Chintya; Nuraeni, Reni (Jurnal Master Pariwisata (JUMPA); Volume 07, Nomor 01, Juli 2020DO - 10.24843/JUMPA.2020.v07.i01.p13, 2020)
This research is motivated by the post eruption of Mount Agung, Bali Province, which resulted in a decrease in tourist visits to Karangasem Regency, especially Tenganan Pegringsingan Village, which entered red zone. In an effort to increase tourism visits to Tenganan Pegringsingan Village after Mount Agung eruption, communication strategy is needed. This study uses a qualitative research methodology with descriptive qualitative approach. The purpose of this study is to determine communication strategy of Karangasem Regency Tourism Office in increasing tourist visits to Tenganan Pegringsingan Village after Mount Agung eruption. The discussion in this study discusses four stages, namely analysis and research by indetifying the problem, reviewing the objectives, and conducting a survey to find out the characteristics of tourists. In policy formulation stage determines the strategy to be used, conducts socialization to Tenganan Pegringsingan Village related to the main strategy being carried out, namely Tenganan Festival, and sets target. At the planning the implementation program stages the main strategy is carried out, started from funds, place, administration, coordination with related parties, the concept of the event, and the personnel involved. The last step is communication, in this stage, the dissemination information related to Tenganan Festival as the main strategy and conducts Tenganan Festival activities. The results of this study found that the strategies carried out could not increase tourist visits. Keywords: Communication strategy, Tourism Village, Communication Planning